-4x+-8x=-5(1-5x)+5(-8x-2)

Simple and best practice solution for -4x+-8x=-5(1-5x)+5(-8x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+-8x=-5(1-5x)+5(-8x-2) equation:


Simplifying
-4x + -8x = -5(1 + -5x) + 5(-8x + -2)

Combine like terms: -4x + -8x = -12x
-12x = -5(1 + -5x) + 5(-8x + -2)
-12x = (1 * -5 + -5x * -5) + 5(-8x + -2)
-12x = (-5 + 25x) + 5(-8x + -2)

Reorder the terms:
-12x = -5 + 25x + 5(-2 + -8x)
-12x = -5 + 25x + (-2 * 5 + -8x * 5)
-12x = -5 + 25x + (-10 + -40x)

Reorder the terms:
-12x = -5 + -10 + 25x + -40x

Combine like terms: -5 + -10 = -15
-12x = -15 + 25x + -40x

Combine like terms: 25x + -40x = -15x
-12x = -15 + -15x

Solving
-12x = -15 + -15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '15x' to each side of the equation.
-12x + 15x = -15 + -15x + 15x

Combine like terms: -12x + 15x = 3x
3x = -15 + -15x + 15x

Combine like terms: -15x + 15x = 0
3x = -15 + 0
3x = -15

Divide each side by '3'.
x = -5

Simplifying
x = -5

See similar equations:

| 13d=25p | | 2600000=.0000113x^3-.000922x^2+.0538x+1.97 | | 9x^2=-11 | | -12m+7m=14-59 | | c^3+10c+25c= | | w*(3w-5)=28 | | 5x-2(x+2)=-1 | | fx=x(50-2x)(30-2x) | | 12=3-0.25p | | 5x+4(2+7)=184 | | W+8(6-w)=13 | | -6.2(4p+6)-1.2(2p-4)= | | 18-72= | | -4*1.5= | | 5x^2+4x-57=0 | | 66=5x+11 | | x^3+7x^2+10x=120 | | 79.50-45.00= | | 6-4y=5y+13 | | 8x^2+43x+15= | | 79.50-45= | | 8x^3+4x^2=0 | | x+(x-12)=208 | | 455+4x=25x | | 4a=7a | | x^3+7x^2+10x-120=0 | | 2x+0y=-6 | | 2-5[h+3]=-28 | | (2c)i+1=-d+6-i | | 24w+48= | | 2(3x+5)=4x+8 | | 2x^2-58x+159=0 |

Equations solver categories